Architecture as a gesture of contemporary culture: Office building, campus of the NCR multinational company, New Belgrade - Lojanica, Vladimir (Arhitektura i urbanizam, 2022)
The NCR campus is the first facility completed within the newly-planned unit of Block 42, according to an urban and architectural competition from 2014, which includes the design of a bus and train station, with an accompanying complex of business facilities and towers. The building in question is a business facility, positioned directly next to the platforms of the railway station, which leans on the existing physical structure with accentuated horizontality, and which has space in front of it reserved for a square, green areas and urban elements. The structure of the building is linear, longitudinal, and defined by the functional and technological conditions of the program and urban parameters, and the public square planned in front of it is an important integrative element in the composition. All of the floors in the facility are exclusively for business use, with offices, and rooms for meetings and presentations, and the necessary accompanying amenities. The facade is characterized by free, sculptural access to glass planes and aluminium brise soleils, and segmenting of the extremely long facade front into smaller units reduces the impression of the size of the building, introducing it to measurable urban dimensions. On the north-eastern facade, facing the square, glass panels of different reflections have been placed at different depths and are intersected with a frame of horizontal and vertical metal brise soleils, creating an impression of spontaneity and irregularity. The facade oriented towards the railway platforms has a more industrial character and accentuated horizontal elements. The quality of the final aesthetic experience of the building was achieved by carefully applying the technical characteristics of the materials and functioning of the adopted details.